Material Characterization of Magnesium Elektron ZRE1 Alloy with Praseodymium (Pr) and Erbium (Er) Additions - Bin Ahmad, Rosli; Mazlan, Nadia Farhana (Research Progress in Mechanical and Manufacturing Engineering, 2020)
The application of magnesium (Mg) is limited due to its poor mechanical and microstructural properties. The additions of rare earth elements to the Mg-Zn-Zr alloys will result in a much better properties of Mg alloy. In this study, the additions of erbium and praseodymium to magnesium elektron ZRE1 will be discussed thoroughly. This study will discuss the effects of praseodymium (Pr) and erbium (Er) on the microstructure and mechanical properties of Mg elektron ZRE1 alloy. Mg elektron ZRE1 alloy was used as main material while Elektron 21, Mg-Gd-Zn and MEZ alloys were used for comparison purposes. As for main rare earth (RE) additives, Praseodymium (Pr) and erbium (Er) were used. Yttrium (Y), gadolinium (Gd) and cerium (Ce) were also used to get more accurate results. This research focused on the case study where results and data from previous research will be analysed and compared to achieve the objectives. RE additions reduce the grain size of alloy and increase its volume fraction. UTS and hardness value were also increased with the additions of RE. The study carried out has shown that the additions of Pr and Er can positively influenced the mechanical and microstructure properties of Mg elektron ZRE1 alloy. Due to the potential of ZRE1 alloy in application such as industrial application, further study should be widely done on this alloy.